8‐3: Development of Highly Efficient RGB Cadmium‐Free Quantum‐Dot Light‐Emitting Diodes. Issue 1 (28th June 2022) - Ryowa, Tatsuya; Sakakibara, Yusuke; Yamamoto, Satoru; Kitano, Keisuke; Iwata, Noboru; Izumi, Makoto; Ogura, Yuko; Michiwaki, Yoko; Nikata, Soichiro; Mishima, Akio; Kalousek, Vit; Takasaki, Mikihiro; et al.
Abstract : This paper reports the highly efficient and high color purity red, green and blue cadmium‐free quantum dots and light‐emitting diodes (QD‐LED). Especially the red and green cadmium‐free QDs have developed with optimized structure. These new QDs have great potential to be used in next generation QD‐LED display with wide color gamut.